SEDIGISM-ATLASGAL: dense gas fraction and star formation efficiency across the Galactic disc. Issue 3 (11th September 2020) - Urquhart, J S; Figura, C; Cross, J R; Wells, M R A; Moore, T J T; Eden, D J; Ragan, S E; Pettitt, A R; Duarte-Cabral, A; Colombo, D; Schuller, F; Csengeri, T; et al.
ABSTRACT: By combining two surveys covering a large fraction of the molecular material in the Galactic disc, we investigate the role spiral arms play in the star formation process. We have matched clumps identified by APEX Telescope Large Area Survey of the Galaxy (ATLASGAL) with their parental giant molecular clouds (GMCs) as identified by SEDIGISM, and use these GMC masses, the bolometric luminosities, and integrated clump masses obtained in a concurrent paper to estimate the dense gas fractions (DGFgmc = ∑ M clump / M gmc ) and the instantaneous star formation efficiencies (i.e. SFEgmc = ∑ L clump / M gmc ). We find that the molecular material associated with ATLASGAL clumps is concentrated in the spiral arms (∼60 per cent found within ±10 km s^-1 of an arm). We have searched for variations in the values of these physical parameters with respect to their proximity to the spiral arms, but find no evidence for any enhancement that might be attributable to the spiral arms. The combined results from a number of similar studies based on different surveys indicate that, while spiral-arm location plays a role in cloud formation and H i to H2 conversion, the subsequent star formation processes appear to depend more on local environment effects. This leads us to conclude that the enhanced star formation activity seen towards the spiral arms is the result of source crowding rather than the consequence of any physical process.